2015
DOI: 10.1111/aor.12500
|View full text |Cite
|
Sign up to set email alerts
|

Posture Influence on the Pendulum Test of Spasticity in Patients with Spinal Cord Injury

Abstract: The study aims to investigate the influence of different postures on spasticity results by pendulum test in patients with spinal cord injury (SCI). The setting was at the University of Campinas (UNICAMP), Campinas, SP, Brazil. Five individuals with SCI and five individuals in the control group were included. All individuals went through the pendulum test in three different positions: supine, semi-supine at an angle of 30°, and sitting up at an angle of 60°. An electrogoniometer was attached to the right leg fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Several studies have shown feasibility of using sensor technologies with an instrumented pendulum test [ 19 , 21 , 28 ] and repeatability and validity for assessing spasticity in patients has generally been reported as positive [ 25 , 29 , 30 ]. Although the test has some drawbacks [ 31 ], such as being sensitive to posture during the test [ 32 , 33 ], clinical evidence is increasing that the pendulum test has value for objectively quantifying spasticity of knee extensors [ 34 – 39 ], as well as flexors and extensor of the elbow [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown feasibility of using sensor technologies with an instrumented pendulum test [ 19 , 21 , 28 ] and repeatability and validity for assessing spasticity in patients has generally been reported as positive [ 25 , 29 , 30 ]. Although the test has some drawbacks [ 31 ], such as being sensitive to posture during the test [ 32 , 33 ], clinical evidence is increasing that the pendulum test has value for objectively quantifying spasticity of knee extensors [ 34 – 39 ], as well as flexors and extensor of the elbow [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pendulum test was performed with subjects in a semireclined position on an adjustable height mat table. Prior work has indicated that similar pendulum test outcomes are produced in individuals with SCI when tested in the fully reclined and semi-reclined positions [24], and the latter position is more comfortable. The test leg was flexed at the knee and hanging over the edge of the mat, the nontest leg was supported on a chair with the knee in extension.…”
Section: Spasticity Assessmentmentioning
confidence: 91%
“…1A). This neutral position helps to avoid increases in spasticity related to the stretching of the rectus femoris or the decrease of spasticity related to less stretched and more relaxed muscle (de Azevedo et al, 2015). The same rater performed all MAS assessments.…”
Section: Methodsmentioning
confidence: 99%